Efeito do extrato aquoso de sete-sangrias [Cuphea mesostemon (Koehne) Lourt] sobre o fluxo de água, medido em bexiga urinária de sapo in vitro - Otake, A. H. [UNESP]; Alves, M. J Q F [UNESP] (My University, 2002)
The Cuphea mesostemon specie, known as sete-sangrias, is widely used as a diuretic substance in popular medicine. As the toad urinary bladder is an epithelium analogous to the distal nephron of mammals, it is used in order to study the transport water and electrolytes in many laboratories. This preparation permits excellent observation in water flow, from the urinary bladder lumen to the external side or the serosal one (water re-absorption), by means of gravimetrical measures. In the present work the hydrosmotic effect of aqueous extract (AE) of sete-sangrias leaf was studied. A 20% solution was added to the serosal side (S) of the bladder preparation, and the water flow was measured every 15 minutes after that. The results showed that 4mL of AE in the S side, increased the JH20 in a significant manner (p<0,05). This effect had a dose - response shape, with the volumes of 0,2mL, 0,4mL and 0,8mL of AE in the S bath. The hydro-osmotic effect of the anti-diuretic hormone (ADH) was studied as well and a significant stimulation (p<0,05) in the JH2O was observed with the magnitude of 150%. The AE effect was similar to the ADH one, and was not antagonized by this hormone. We concluded that Cuphea possesses an anti-diuretic activity similar to that presented by ADH, in toad urinary bladder, in vitro.
Effect of aqueous extract of sete-sangrias (Cuphea mesostemon (Koehne) Lourt) on the water flow, measured in toad urinary bladder in vitro
Keywords: Cuphea mesostemon; Sete-sangrias and antidiuretic hormone; Toad urinary bladder; Water flow; Cuphea mesostemon extract; plant extract; unclassified drug; vasopressin; animal tissue; bladder; diuresis; dose response; medicinal plant; membrane permeability; nonhuman; sodium transport; toad; water flow